Inclusive development in fostering social safety net for disable people and women in Malaysia - Quddus, S. M. Abdul (2019)
Social Safety Net (SSN) is one of affirmative action by the Malaysia government in fostering the inclusive development for disadvantaged groups. Since the “1969 crisis’ and the Asian Financial Crisis of 1997, Malaysia has successfully transformed and developed itself from a developing country to a middle-income nation with the aim to provide equal opportunity for every citizen. Due to the multi-racial and multi-religious population inhabited in Malaysia, thus, there are always discussion on race, religion, inequality and vulnerability in the Malaysian society. This research is aimed to focus on three things: firstly, discuss government policies in assisting the disadvantaged group in the society, especially disabled people and women; secondly, our study intended to examine the effectiveness of government programs and policies in line with the inclusive development strategy of the government. Thirdly, the study also wants to identify and analyse challenges relating to SSN policy of Malaysia in fostering inclusive development. Data for this study collected from government websites in particular, website of the Ministry of Women, Family and Community Development, academic journals and published articles. This study has shown what actions government should be taken and embarked at the policy level in promoting inclusiveness of marginalized people in the society such as a disabled person and women.